Chemical Oscillation and Morphological Oscillation in Catalyst-Embedded Lyotropic Liquid Crystalline Gels - Li, Guanying; Cortes, William; Zhang, Qizheng; Zhang, Ye (Frontiers in Chemistry, 2020)
Liquid crystalline gels offer promising means in generating smart materials due to programmable mechanics and reversible shape changes in response to external stimuli. We demonstrate a simple and convenient method of constructing catalyst-embedded lyotropic liquid crystalline (LLC) gels and achieve chemomechanical oscillator by converting chemical waves in Belousov-Zhabotinsky (BZ) reaction. We observe the directed chemical oscillations on LLC sticks accompanied by small scale oscillatory swellings-shrinkages that is synchronized with the chemical waves, of an LLC stick. To amplify the mechanical oscillations, we further fabricate small LLC fibers and achieve macroscopically oscillatory bending-unbending transition of the LLC fiber driven by a BZ reaction.